Determinants Of The Incident Of Pulmonary Tb Disease Transmission In Families Living In The Same House At Putri Hijau Tk Ii Hospital, Medan, 2023 - Syafrita Sundari; Kesaktian Maurung; Rinawati Sembiring (SEAN Institute, 2023)
Tuberculosis is a direct infectious disease caused by Mycobacterium tuberculosis, most of the tuberculosis germs attack the lungs, but also affect other organs of the body. Tuberculosis is a health problem with a very high incidence and is a global health problem today. The healthy and sick status of family members and families influence one another. A disease that runs in a family affects the whole family and in turn affects the course of the disease and the status of family members. Therefore, the influence of the health/sickness status on the family influences or is highly dependent on one another. Family behavior in prevention plays an important role in reducing the risk of pulmonary TB transmission. The increasing number of pulmonary TB patients in Indonesia is caused by unhealthy behavior. The formulation of the problem in this study is the determinants of the incidence of pulmonary TB transmission in families who live in the same house at Putri Hijau Tkt Hospital. II Medan in 2023. The type of research is observational analytic research using the cross-sectional method, namely the independent variables and the dependent variable are observed simultaneously. The sample used in this study was a total sample or total sampling of 52 people. The results in this study indicate that there is no relationship between age and a P-value of 0.084, there is a relationship between gender and a P-value of 0.000, there is a relationship between work and a P-value of 0.001, there is a relationship between knowledge and a P-value of 0.001, There is a relationship between smoking habits with a P-value of 0.001, There is a relationship between nutritional status and a P-value of 0.001, There is a relationship between contact history and a P-value of 0.001. The most dominant factor related is the history of contact with Exp (B ) 108,168 in the prevention of pulmonary TB transmission in families at Putri Hijau Tkt Hospital. II Medan in 2023.